Locke, science and politics - Forde, Steven, 1954- (Cambridge : Cambridge University Press, 2013)
'In this ground-breaking book, Steven Forde argues that John Locke's devotion to modern science deeply shaped his moral and political philosophy. Beginning with an account of the classical approach to natural and moral philosophy, and of the medieval scholasticism that took these forward into early modernity, Forde explores why the modern scientific project of Francis Bacon, Pierre Gassendi, Robert Boyle and others required the rejection of the classical approach. Locke fully subscribed to this rejection, and took it upon himself to provide a foundation for a compatible morality and politics. Forde shows that Locke's theory of moral'mixed modes' owes much to Pufendorf, and is tailored to accommodate science. The theory requires a divine legislator, which in turn makes natural law the foundation of morality, rather than individual natural right. Forde shows the ways that Locke's approach modified his individualism, and colored his philosophy of property, politics, and education'--
Machine generated contents note: Introduction; 1. Science and morality; 2. Locke's moral epistemology; 3. The paradoxes of Locke's moral and political teaching; 4. Conclusion: some thoughts concerning education and Lockean happiness.
Includes bibliographical references and index.
Keywords: Locke, John, -- 1632-1704.; Science -- Moral and ethical aspects; Natural law; Political science -- Philosophy